2018
DOI: 10.1101/310250
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Identification of midbrain neurons essential for vocal communication

Abstract: 8Vocalizations are an essential medium for communication and courtship in numerous 9 mammalian species ranging from mice to humans. In mammals, the midbrain PAG serves as 10 an obligatory node in a vocalization-related network that spans the forebrain and brainstem 1-3 , 11as bilateral lesions of the PAG result in mutism 2-5 . Despite the PAG's importance for vocal 12 production, the identity, function, and connectivity of PAG neurons involved in vocalization has 13 remained elusive, in part because the PAG is… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…The comparison we performed between the outcomes of SB transposon mutagenesis carried out in the present Alb-R26 Met genetic setting and in other settings[21, [31][32][33][34][35] revealed that among the 275 Alb-R26 Met -transposon genes, aside from a large group of common hits, 49 genes were only found in the Alb-R26 Met context, which we named 'putative RTK-specific genes'. For a proportion of them, it is possible that they could have been missed in previous screens because transposon mutagenesis does not reach saturation levels, particularly with small numbers of analysed tumours.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The comparison we performed between the outcomes of SB transposon mutagenesis carried out in the present Alb-R26 Met genetic setting and in other settings[21, [31][32][33][34][35] revealed that among the 275 Alb-R26 Met -transposon genes, aside from a large group of common hits, 49 genes were only found in the Alb-R26 Met context, which we named 'putative RTK-specific genes'. For a proportion of them, it is possible that they could have been missed in previous screens because transposon mutagenesis does not reach saturation levels, particularly with small numbers of analysed tumours.…”
Section: Discussionmentioning
confidence: 99%
“…Next, we assessed the level of specificity in gene cooperation with enhanced MET levels by comparing the Alb-R26 Met -transposon genes with those identified in other liver SB screens: p53 mut [21]), Myc over [31], HBV tg [32], chemically induced chronic liver injury [33], hepatic steatosis [34], epithelial-mesenchymal transition [35]. Among the 275 Alb-R26 Met -transposon genes, 226 (82%) were found in one or more SB screen cohorts.…”
Section: Comparison To Other Sb-induced Cancer Liver Models Identifiementioning
confidence: 99%